Plants of the Russian Federation pharmacopeia: an unexhausted natural products research opportunity?. Issue 21 (2nd November 2021) - Chupakhin, Evgeny; Babich, Olga; Prosekov, Alexander; Asyakina, Lyudmila; Gureev, Maxim; Krasavin, Mikhail
Abstract: 32 medicinal plants that are unique to the Russian Pharmacopeia have 693 isolated natural products associated with them (an average of 21.66 compounds per plant). This is in contrast to the US Pharmacopeia plants that have delivered 2366 known natural products (an average of 42.25 compounds per plant). Graphical Abstract: